2018
DOI: 10.5455/handmicrosurg.266188
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and predictors in simple decompression of ulnar nerve entrapment at the elbow

Abstract: Objectives:Simple decompression is an accepted surgical treatment of ulnar nerve entrapment at the elbow (UNE). Our purpose was to evaluate the outcome and potential predictors for the outcome after simple decompression in UNE. Methods: All surgically treated UNE cases (from 2004-2008) at our department were studied retrospectively. Out of 285 primary surgeries, 242 primary simple ulnar nerve decompressions were included. Medical records, including electrophysiologic protocols, were reviewed and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Apart from the duration of symptoms before surgery (p < 0.05), there were no statistically significant variations in preoperative clinical data between both groups. The current results agree with Said et al 26 and Anker et al 27 With a sensitivity of 37 to 100%, motor NCS in patients have revealed localizing anomalies in symptomatic elbows. Campbell et al 28 found sensitivity of 53 to 56% in severe cases and 27% in moderate cases.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from the duration of symptoms before surgery (p < 0.05), there were no statistically significant variations in preoperative clinical data between both groups. The current results agree with Said et al 26 and Anker et al 27 With a sensitivity of 37 to 100%, motor NCS in patients have revealed localizing anomalies in symptomatic elbows. Campbell et al 28 found sensitivity of 53 to 56% in severe cases and 27% in moderate cases.…”
Section: Discussionsupporting
confidence: 93%
“…A limitation of the study is the lack of serial measurements to assess changes in biomarkers and risk factors over time, and that the time lapse from biomarker measurement to diagnosis is long. The population of the cohort is elderly (the youngest participant was 46 years old at study start), and nerve compression disorders, such as CTS and UNE, usually occur at 45-65 years of age (Atroshi, 2011;Anker et al, 2018;Giöstad and Nyman, 2019). The peak incidence of CTS in a general population in Sweden is in individuals aged 45-54 years (Atroshi et al, 1999;Atroshi, 2011), and the corresponding incidence of UNE in an American National Database is in individuals aged 61-65 years (Osei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The HAKIR register does not provide information on how a diagnosis is made. In Sweden, CTS diagnosis is supported by electrophysiological examination in approximately 70% of cases [19] and in UNE in approximately 80% of cases [20]; in the rest of the cases, diagnosis is based on patient history and clinical examination.…”
Section: Methodsmentioning
confidence: 99%
“…There were 222 women (37%) and 296 men (45%) who never had received social assistance. In both men and women, manual workers had more sick leave than non-manual workers; female non-manual workers' mean days/employed year was 30 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) vs. female manual workers, 39 (33-45; p < 0.001); male non-manual workers, 20 (17)(18)(19)(20)(21)(22)(23) vs. male manual workers, 28 (24-31; p < 0.001). Preoperative QuickDASH scores were higher in women than in men (Table 3), both for decompressions and transpositions (p < 0.001).…”
Section: Ulnar Nerve Entrapment At the Elbowmentioning
confidence: 99%